Periodic evolution of the ionomer/catalyst interfacial structures towards proton conductance and oxygen transport in polymer electrolyte membrane fuel cells. (September 2020) - Sun, Ruili; Xia, Zhangxun; Xu, Xinlong; Deng, Ruoyi; Wang, Suli; Sun, Gongquan
Abstract: The construction of electrochemical boundaries involving pathways for oxygen, proton and electron within catalyst layers dominates the fuel cell performance especially at ultralow precious metal loadings. However, the intrinsic relationships between electrochemical processes and nano-/subnano-structures of the interfaces containing perfluorosulfonic acid ionomers (e.g. Nafion) and platinum decorated carbon catalysts have remained in a vague picture. Here in this work, precise details of Nafion/Pt interfacial structures in multiscale are investigated with their coverage architecture in varied ionomer/carbon ratios. The electrochemical processes involving proton migration and oxygen transport within such Nafion/Pt interfacial structures are revealed by in-situ analyses. A periodic evolution of the interfacial properties towards proton/oxygen transport is demonstrated within the increase of the covered Nafion layers. Such phenomena could be derived from the alternately exposure of the hydrophilic and hydrophobic phases of the sandwich structure of Nafion ionomer. Graphical abstract: Nafion/Pt interfacial structures and properties are researched and oxygen/proton transport resistance shows a periodic change for the alternative exposure of Nafion/Pt interfacial structures. Image 1 Highlights: Interfacial structure of Nafion/Pt is adjusted via varied ionomer/carbon ratios. Proton conductivity in CL is affected by ionomer coverage and layer thickness. Oxygen interfacial transport resistance is affected by Nafion/Pt structures. Periodic evolution of ionomer layers is proofed via ionomer alternately exposed.